Sheep health, welfare and production planning 3. Using financial indicators. Issue 4 (3rd April 2014) - Wright, Nerys; Phythian, Clare; Phillips, Kate; Morgan, Mair
Abstract : Implementing changes to sheep vaccination programmes, parasite control and flock nutrition often incur additional cost in advance of any improvements in performance. This article, the last in a series of three examining the opportunities for veterinary practitioners and livestock advisors to engage more sheep farmers in active health planning, looks at calculating the financial gain of implementing changes to improve flock performance, which is crucial to ensuring that farmers realise the benefits resulting from the initial investment.